Impact of lymphocytic thyroiditis on incidence of pathological incidental thyroid carcinoma. Issue 1 (28th October 2016) - Farrell, Eric; Heffron, Cynthia; Murphy, Matthew; O'Leary, Gerard; Sheahan, Patrick
Abstract: Background: The purpose of this study was to investigate the impact of lymphocytic thyroiditis on incidence of incidental thyroid cancers. Methods: We conducted a retrospective review of 713 consecutive patients who underwent thyroidectomies. Incidental thyroid cancer was defined as an unexpected cancer discovered on pathological examination outside the index nodule undergoing preoperative cytology. Results: We excluded 65 cases because of preoperative diagnosis of thyroid cancer, and 68 because of nonincidental cancer within the index nodule. Among the remaining 580 cases, there were 43 cases (7.4%) of incidental thyroid cancers. Incidental thyroid cancers were significantly associated with moderate/severe lymphocytic thyroiditis (relative risk = 2.5; p  = .03). Sixteen of 56 patients with moderate/severe lymphocytic thyroiditis had Graves' disease, none of whom had incidental thyroid cancer. The risk of incidental thyroid cancer associated with moderate/severe lymphocytic thyroiditis was significantly higher in non‐Graves' than patients with Graves' disease ( p  = .05). Conclusion: The risk of incidental thyroid cancer is significantly increased in patients with moderate/severe lymphocytic thyroiditis. Moderate/severe lymphocytic thyroiditis associated with Graves' disease seems to have a lower risk of incidental thyroid cancer. © 2016 Wiley Periodicals, Inc. Head Neck 39: 122–127, 2017